Marketing Strategy in Increasing Product Sales at PT Avipen Adhitama Industries in Tangerang City - Haryantini; Priyantini Dewi (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze marketing strategies in increasing product sales at PT Avipen Adhitama Industries in Tangerang City. The research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the company implements a marketing mix (4P) strategy consisting of product, price, place, and promotion. The product strategy focuses on quality and variety, pricing is competitive, distribution is carried out through store and project channels, and promotion is primarily conducted through direct selling and limited digital media. However, several challenges have been identified, such as low brand awareness and limited utilization of digital marketing. The study concludes that while the current strategy is relatively effective, improvements in digital promotion and market expansion are necessary to enhance sales performance sustainably.